A comparison of the Objective Structured Clinical/ Practical Examination (OSCE/OSPE) Scores of the Biochemistry Laboratory Obtained by Male and Female Nursing Students of Shahid Beheshti University of Medical Sciences: 2011-15 - Hosseini, Saeedeh; Vartanoosian, Jacqueline; Hosseini, Fatemeh; Faridi, Zhila (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: The Objective Structured Clinical/Practical Examination (OSCE/OSPE) is one of the best assessment methods for measuring the students’ realization of their educational goals in cognitive, emotional, and psychomotor domains. Given that gender may influence the evaluation of medical sciences examinations, the present study was conducted to compare the female and male nursing students of Shahid Beheshti University of Medical Sciences during years 2011 to 2015 in terms of their OSCE/OSPE scores for the biochemistry laboratory. Methods: This study had a comparative descriptive design. All of the students participated in this study from 2011 to 2015 (census). Over these four years, 649 students took this examination and their scores were recorded. The data collection tools included a demographic information questionnaire and a researcher-made checklist. Pearson’s Correlation Coefficient was calculated for determining both the criterion validity and the internal consistency (r = 0.732). The Pearson correlation coefficient confirmed the testretest reliability of the test (r = 0.88). The data were analyzed using the SPSS-22 software with descriptive statistics, the independent t-test, the one- way Analysis of Variance (ANOVA), and Scheffe’s post-hoc test. Results: The scores of 361 female students and 288 male students were assessed in this study. The mean score was 11.6 ± 1.83 in female students and 11.2 ± 1.75 in male students (out of 14). The difference between the female and male students’ OSCE/OSPE scores in biochemistry laboratory skills was significant (P = 0.02). Comparing the mean scores of the female and male students in biochemistry laboratory skills according to OSCE/OSPE by year of admission showed a significant difference between the genders in the students admitted to the school during year 2012 (P = 0.01). There were also significant differences between the age groups of < 20 and 25-29 and the other age groups in terms of the mean OSCE/OSPE scores (P < 0.05). Conclusions: There was a significant difference between the two genders in the mean crude scores obtained and the female students had slightly higher scores. Future studies are recommended to investigate the students of other disciplines, academic levels, and schools to improve the generalizability of these findings.